Kombinasi Metode Operational Competitiveness Rating Analysis (OCRA) dan Rank Order Centroid (ROC) Dalam Pemilihan Studio Photo Terbaik - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
There are many businesses in the field of photography services that are in demand among the public, resulting in many requests from people who want to document certain memorable moments. Seeing the large number of people who want to immortalize every moment, this creates many opportunities for people who have expertise in this field and want to do business in this field and open new photo studios. Each photo studio has its own way of attracting people's attention, many photo studios also have different promotions in offering their services, both in terms of price and quality provided, which makes people confused in choosing a photo studio. In this research, we will utilize a Decision Support System (SPK) which is an alternative in determining the best photo studio. In determining the best photo studio, you must determine several necessary criteria such as service, facilities, price, customer satisfaction and quality. Therefore, we need a Decision Support System that uses the ROC (Rank Order Centroid) method and the OCRA (Operational Competitiveness Rating Analysis) method to overcome existing problems. So that you get a weight value and you will also get the highest preference value from several choices. So we get the best alternative A8, namely Key Photography with a preference value of 0.495.